The American species of Escaryus, a genus of holarctic centipeds (Geophilomorpha: schendylidae) - Pereira, Luis Alberto (1993)
Eight North American species of Escaryus are regarded as valid. A historical summary is provided for the genus, as well as observations on the taxonomic significance of various characters heretofore utilized to distinguish genera of schendylids. Known Palearctic taxa are listed. Escaryus ethopus Chamberlin, E. liber Cook & Collins, E. missouriensis Chamberlin, E. monticolens Chamberlin, E. paucipes Chamberlin, and E. urbicus (Meinert) are redescribed and figured from type material and/or additional specimens. Escaryus delus Chamberlin is considered to be a junior synonym of E. ethopus. Escaryus cryptorobius and E. orestes are described as new species, both from Whitetop Mountain, Virginia. Escaryus japonicus is removed from the North American list, the Alaskan specimen upon which Chamberlin’s 1952 record was based having been found to be an individual of E. ethopus. Examination of type material of species thought possibly referable to Escaryus shows that the nominal genera Lionyx Chamberlin 1960 and Zygona Chamberlin 1960, originally proposed in the Schendylidae, must be referred instead to the Geophilidae.